Nominative Linkage of Records of Officials in the China Government Employee Dataset-Qing (CGED-Q) - Campbell, Cameron; Chen, Bijia (Historical Life Course Studies, 2022)
We introduce our approach to the nominative linkage of records of Qing officials who were included in the China Government Employee Datasets-Qing (CGED-Q) Jinshenlu (JSL) and Examination Records (ER). We constructed these datasets by transcription of quarterly rosters of civil and military officials produced by the government and by commercial presses, and records of examination degree holders. We assess each of the primary attributes available in the original sources in terms of their usefulness for disambiguation, focusing on their diversity and potential for inconsistent recording. For officials who were not affiliated with the Eight Banners, these primary attributes include surname, given name, and province and county of origin. For the small subset of officials who were affiliated with the Bannermen, we assess the available data separately. We also assess secondary attributes available in the data that may be useful for adjudicating candidate matches. We then describe the approach that we developed that addresses the issues we identified with the primary and secondary attributes. The issues we have identified and the approach that we have developed will be of interest to researchers engaged in similar efforts to construct and link datasets based on elite males in historical China.